2006
DOI: 10.1098/rspb.2006.3641
|View full text |Cite
|
Sign up to set email alerts
|

Can the common brain parasite,Toxoplasma gondii, influence human culture?

Abstract: The latent prevalence of a long-lived and common brain parasite, Toxoplasma gondii, explains a statistically significant portion of the variance in aggregate neuroticism among populations, as well as in the 'neurotic' cultural dimensions of sex roles and uncertainty avoidance. Spurious or non-causal correlations between aggregate personality and aspects of climate and culture that influence T. gondii transmission could also drive these patterns. A link between culture and T. gondii hypothetically results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 38 publications
3
83
0
3
Order By: Relevance
“…Prevalence of latent toxoplasmosis in women of childbearing age in various countries. Third column shows prevalence (%) adjusted to a standard age of 22 years to account for variation in childbearing age across countries using the formula Prevalence adj = 1 -(1 -Prevalence)^(22/childbearing age) (Lafferty, 2006). Year in which the given study has been carried out is shown in the fourth column, the fifth column states the number of women in the sample and the last one gives sex ratio at birth (SRB).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Prevalence of latent toxoplasmosis in women of childbearing age in various countries. Third column shows prevalence (%) adjusted to a standard age of 22 years to account for variation in childbearing age across countries using the formula Prevalence adj = 1 -(1 -Prevalence)^(22/childbearing age) (Lafferty, 2006). Year in which the given study has been carried out is shown in the fourth column, the fifth column states the number of women in the sample and the last one gives sex ratio at birth (SRB).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Even an equivalent of the fatal feline attraction phenomenon observed in infected rats (Berdoy et al, 2000) has been identified in humans, where T. gondii-positive humans showed altered questionnaire responses to the odours of the domestic cat (and of the brown hyena) (Flegr et al, 2011). Such subtle changes in human behaviour and personality in response to latent T. gondii infection at the individual level have even been proposed to alter the human aggregate personality at the population level (Lafferty, 2006). Latent T. gondii infection in the human host may, furthermore, in a small number of cases, have substantial health implications.…”
Section: Current Evidence For T Gondii Manipulation Of Intermediate mentioning
confidence: 99%
“…Behaviour and infection are intimately linked because parasites can affect behaviour, perhaps even influencing human personalities and contributing to cultural differences [8], and many individual host behaviours have been separately shown to impact chances of infection [9,10]. However, very few studies of behavioural syndromes have examined whether animal 'personalities' predict susceptibility to parasitism [11,12], and none have done so experimentally.…”
Section: Introductionmentioning
confidence: 99%